Postoperative Complications and Short‐Term Outcome Following Single‐Session Bilateral Corrective Surgery for Medial Patellar Luxation in Dogs Weighing <15 kg: 50 Cases (2009–2014). Issue 7 (2nd August 2016) - Gallegos, Javier; Unis, Marcos; Roush, James K.; Agulian, Lori
Abstract : Objective: To assess complication rates and short‐term outcome in small dogs with bilateral medial patellar luxation (MPL) undergoing single‐session bilateral corrective surgery. Study Design: Retrospective case series. Animals: Dogs weighing <15 kg with congenital bilateral MPL that underwent single‐session bilateral corrective surgery (n = 50). Methods: Surgical procedures for MPL correction included trochlear wedge recession (TWR), crest transposition, lateral imbrication, and medial fascial release. Complication rates were correlated with number of surgical procedures, weight, whether or not a bandage was applied postoperatively, and surgeon experience (ACVS Diplomate vs resident). Results were compared with the most recent study evaluating single‐session bilateral corrective surgery for MPL. Results: Overall complication rate was 22% (11 of 50 dogs). Implant failure occurred in 2 dogs (3 stifles) requiring revision. Grade 1 patella reluxation was the most common minor complication at 10% (5/50). Overall complication and reluxation rates were similar to previous studies. There were no intraoperative complications after performing TWR in small dogs. Conclusion: Single‐session bilateral corrective surgery for MPL is well tolerated in small dogs with complication rates historically similar to dogs undergoing unilateral or staged bilateral surgery. With individual case assessment, single‐session surgery could be offered to owners, allowing one anesthetic episode and potentially lowering the chance for morbidity. Further studies, ideally prospective studies, are needed to assess long‐term outcome following single‐session bilateral corrective surgery for MPL.